Stock market reactions to Brexit: Case of selected CEE and SEE stock markets - Tihana Škrinjarić (International Journal of Financial Studies, 2019)
The debate on the UK leaving the European Union is still hot and ongoing today due to many economic, political, social, and other consequences on many different countries over the world. This paper focuses on the reactions of selected Central and Eastern European (CEE) and South and Eastern European (SEE) stock markets to the Brexit vote on 23 June 2016. Using daily data for the time span from January 2010 until July 2016 and the event study methodology (ESM), the return and volatility series are being tested for significant reactions to the Brexit event. The results indicate mixed results regarding the abnormal cumulative return series, but the volatility series were found to be significantly affected by the mentioned event. This is important for international investors and gives information on the reaction of mentioned markets to big political and economic events in order to tailor international portfolios in a way to hedge from risk.
Keywords: C12; C58; G14; 330; Brexit; stock market reaction; event study; emerging markets; abnormal return; abnormal volatility